A Survey on the Challenges of Impacts on Applying for a Job in Ho Chi Minh City - Dan Thanh Do (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
In the 4.0 context, machines gradually replace humans in most fields. The job market becomes depleted in inverse proportion to the abundant human resources. With hundreds of thousands of people unemployed each year, the rate of competition for job vacancies increases accordingly. Countless impacts decline the performance rating, causing fatal flaws that lead to a poor impression on the employers. Employers will receive countless Curriculum Vitals (CVs) to choose from for a job vacancy. How to surpass the competition and catch the eye of employers? This survey was conducted to discover and analyze the difficulties of applying for a job besides participating in a job interview in Ho Chi Minh City. Besides, the author wants to provide a comprehensive insight into recruitment and human resources in this city. A total of 125 candidates were selected from different professions in Ho Chi Minh City to collect information for this survey. Information collected from the questionnaires consisting of 11 small questions was coded and analyzed quantitatively. The final analysis pointed out the objective and subjective factors affecting the application process. In addition, the psychological abnormality affecting the ability to communicate in answering of the interviewers' questions was an outstanding result in the survey. Due to these factors, most of the candidates were rejected from job vacancies. Employers in Ho Chi Minh City consider human resources with a lot of working experience and relationships as an advantage. The goal of this survey that aims to aid candidates in awareness of their problems enhances the success rate in conquering employers.